Partial recovery of senescence and differentiation disturbances in CD8+ T cell effector‐memory cells in HIV‐1 infection after initiation of anti‐retroviral treatment. (23rd August 2016) - Eberhard, J. M.; Ahmad, F.; Hong, H. S.; Bhatnagar, N.; Keudel, P.; Schulze zur Wiesch, J.; Schmidt, R. E.; Meyer‐Olson, D.
Summary: Immune senescence as well as disturbed CD8 + T cell differentiation are a hallmark of chronic HIV infection. Here, we investigated to what extent immune senescence is reversible after initiation of anti‐retroviral treatment (ART). Peripheral blood mononuclear cells (PBMCs) from a cohort of HIV patients with different disease courses, including untreated viral controllers ( n = 10), viral non‐controllers ( n = 16) and patients on ART ( n = 20), were analysed and compared to uninfected controls ( n = 25) by flow cytometry on bulk and HIV‐specific major histocompatibility complex (MHC) class I tetramer + CD8 + T cells for expression of the memory markers CCR7 and CD45RO, as well as the senescence marker CD57 and the differentiation and survival marker CD127. Furthermore, a subset of patients was analysed longitudinally before and after initiation of ART. Frequencies of CD57 + CD8 + T cells decreased after initiation of ART in central memory (Tcm) but not in effector memory T cell populations (TemRO and TemRA). The frequency of CD127 + CD8 + cells increased in Tcm and TemRO. We observed a reduction of CD127 – T cells in Tcm, TemRO and partially in TemRA subsets after initiation of ART. Importantly, HIV‐specific CD8 + TemRO cells predominantly displayed a CD127 – CD57 + phenotype in untreated HIV‐patients, whereas the CD127 + CD57 – phenotype was under‐represented in these patients. The frequency of the CD127 + CD57 – CD8 + T cell subpopulation correlated strongly with absolute CD4 + counts in HIV‐infected patients before and after initiation of ART. These findings can be interpreted as a phenotypical correlate of CD8 + memory T cell differentiation and the premature 'ageing' of the immune system, which was even observed in successfully virally suppressed HIV patients. Abstract : We observe a restoration of CD127 expression on all CD8+ T cell memory subpopulations, whereas the increased expression of the senescence marker CD57 on CD8+ effector memory T cell subsets in chronic HIV infection is not reversible after initiation of ART. Importantly, the frequencies of CD127+CD57‐CD8+TemRO cells correlated with the absolute CD4+ T cell counts, thus supporting the hypothesis that this population might be a correlate for successful immune reconstitution.